2019
DOI: 10.1016/j.fertnstert.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Metformin decreases bone turnover markers in polycystic ovary syndrome: a post hoc study

Abstract: Objective: To study the effects of metformin treatment on bone turnover in women with polycystic ovary syndrome (PCOS), as measured by serum concentrations of bone turnover markers. Design: Post hoc study of a previously conducted prospective multicenter, placebo-controlled, randomized study. Setting: University clinic. Patient(s): The study cohort consisted of 74 non-obese women (body mass index < 27 kg/m 2) and 44 obese women (body mass index R 27 kg/m 2) diagnosed with PCOS, with a mean age of 27.6 AE 4.0 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 49 publications
1
30
1
Order By: Relevance
“…Consistent with the literature, this research found that participants who reported that metformin use is involved in a lower risk of osteoporosis in adult women independent of type 2 diabetes mellitus and obesity [ 11 , 41 ]. This also accords with our earlier observations, which showed that the metformin decreased bone turnover marker and influence bone formation in clinical studies [ 42 , 43 ]. However, we have also noticed that the effect of metformin on bone metabolism is significantly weaker than the use of alendronate, so the use of metformin alone in the treatment of diabetic osteoporosis may require further verification.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the literature, this research found that participants who reported that metformin use is involved in a lower risk of osteoporosis in adult women independent of type 2 diabetes mellitus and obesity [ 11 , 41 ]. This also accords with our earlier observations, which showed that the metformin decreased bone turnover marker and influence bone formation in clinical studies [ 42 , 43 ]. However, we have also noticed that the effect of metformin on bone metabolism is significantly weaker than the use of alendronate, so the use of metformin alone in the treatment of diabetic osteoporosis may require further verification.…”
Section: Discussionsupporting
confidence: 93%
“…However, there are some studies reporting the side effect of metformin on bone. A post hoc study reported that metformin decreased the level of bone turnover factors and hindered the bone remodeling in polycystic ovary syndrome [50]. This effect may compromise the self-repair of minor bone tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…The bone mass and bone mineral content were decreased in the PCOS group, and bone mineral density has been found to be lower in lean patients than in matched controls [70]. In the cohort study of Lingaiah et al, metformin treatment, when compared with a placebo, was related with reduced bone turnover, as suggested by reductions in markers of bone formation and resorption, leading to slower bone remodeling in premenopausal women with PCOS [71].…”
Section: Discussionmentioning
confidence: 99%